Escaping the Phagocytic Oxidative Burst: The Role of SODB in the Survival of Pseudomonas aeruginosa Within Macrophages - Cavinato, Luca; Genise, Elena; Luly, Francesco R.; Di Domenico, Enea G.; Del Porto, Paola; Ascenzioni, Fiorentina (Frontiers in Microbiology, 2020)
Reactive oxygen species (ROS) are small oxygen-derived molecules that are used to control infections by phagocytic cells. In macrophages, the oxidative burst produced by the NOX2 NADPH-oxidase is essential to eradicate engulfed pathogens by both oxidative and non-oxidative killing. Indeed, while the superoxide anion (O2-) produced by NOX2, and the other ROS derived from its transformation, can directly target pathogens, ROS also contribute to activation of non-oxidative microbicidal effectors. The response of pathogens to the phagocytic oxidative burst includes the expression of different enzymes that target ROS to reduce their toxicity. Superoxide dismutases (SODs) are the primary scavengers of O2-, which is transformed into H2O2. In the Gram-negative Salmonella typhimurium, periplasmic SODCI has a major role in bacterial resistance to NOX-mediated oxidative stress. In Pseudomonas aeruginosa, the two periplasmic SODs, SODB, and SODM, appear to contribute to bacterial virulence in small-animal models. Furthermore, NOX2 oxidative stress is essential to restrict P. aeruginosa survival in macrophages early after infection. Here, we focused on the role of P. aeruginosa SODs in the counteracting of the lethal effects of the macrophage oxidative burst. Through this study of the survival of sod mutants in macrophages and the measurement of ROS in infected macrophages, we have identified a dual, antagonistic, role for SODB in P. aeruginosa survival. Indeed, the survival of the sodB mutants, but not of the sodM mutants, was greater than that of the wild-type (WT) bacteria early after infection, and sodB-infected macrophages showed higher levels of O2- and lower levels of H2O2. This suggests that SODB contributes to the production of lethal doses of H2O2 within the phagosome. However, later on following infection, the sodB mutants survived less that the WT bacteria, which highlights the pro-survival role of SODB. We have explained this defensive role through an investigation of the activation of autophagy, which was greater in the sodB-infected macrophages.